2023
DOI: 10.3390/nu15122672
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Omega 3 and Omega 6 Fatty Acids on Glucose Metabolism: An Updated Review

Filippo Egalini,
Ornella Guardamagna,
Giulia Gaggero
et al.

Abstract: Massive changes have occurred in our diet. A growing consumption of vegetal oils rich in omega-6 (ω-6) and a depletion of omega-3 (ω-3) fatty acids (FAs) in our food has led to an imbalance between ω-3 and ω-6. In particular, eicosapentaenoic (EPA)/arachidonic acid (AA) ratio seems to be an indicator of this derangement, whose reduction is associated to the development of metabolic diseases, such as diabetes mellitus. Our aim was therefore to investigate the literature on the effects of ω-3 and ω-6 FAs on gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 115 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…There has also been evidence relating n-6 and n-3 PUFAs intake to cardiometabolic outcomes ( 22 , 45 ), though there are inconsistent findings here as well, particularly because of observations that higher n-6 PUFA intake is associated with lower cardiovascular risks ( 46 ). Our dietary intervention, lower in n-6 PUFA and higher in n-3 PUFA, resulted in multiple cardiometabolic and hormonal improvements, including intentional weight loss without signs of disease progression, reduced total and LDL cholesterol, insulin resistance, free testosterone, and IGF-1 ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
“…There has also been evidence relating n-6 and n-3 PUFAs intake to cardiometabolic outcomes ( 22 , 45 ), though there are inconsistent findings here as well, particularly because of observations that higher n-6 PUFA intake is associated with lower cardiovascular risks ( 46 ). Our dietary intervention, lower in n-6 PUFA and higher in n-3 PUFA, resulted in multiple cardiometabolic and hormonal improvements, including intentional weight loss without signs of disease progression, reduced total and LDL cholesterol, insulin resistance, free testosterone, and IGF-1 ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
“…Reliable sources of omega-3 fatty acids are fish, such as salmon, tuna, mackerel, anchovies, and sardines [262]. The recommended daily intake ranges from 250 to 500 mg per day and depends on gender and age [263]. Omega-3 polyunsaturated fatty acids (n3-PUFAs), mediators of inflammation and adaptive immune responses, have anti-inflammatory and antioxidant properties [110,264].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…[62] Although omega-6 fatty acids are essential, an imbalance in the ratio with omega-3 fatty acids may contribute to inflammation and other health concerns. [63] The inflammatory effects of corn oil are considered debatable, and the available data from studies on omega 6 do not align with the notion that higher intake of this specific fatty acid is detrimental. [64] It was reported that high levels of corn oil significantly increased the longevity of aged mice compared to those on a normal diet.…”
Section: Composition and Health Considerationsmentioning
confidence: 99%